Strings, Branes and Dualities 1999
DOI: 10.1007/978-94-011-4730-9_7
|View full text |Cite
|
Sign up to set email alerts
|

Connections between M-Theory and Superstrings

Abstract: ABSTRACT:This article reviews the non-perturbative structure of certain higher derivative terms in the type II string theory effective action and their connection to one-loop effects in eleven-dimensional supergravity compactified on a torus. New material is also included that was not presented in the talks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…One might hope that some extrapolation of our approach could shed further light on the discussion of [29]. in other recent studies of non-perturbative contributions to string scattering amplitudes [30][31][32][33] it was suggested that D-particle loops are related via T-duality to D-instanton contributions in IIB string theory. It clearly would be interesting to see if the suggestive formulas obtained in these works can possibly be reproduced via the Matrix string methods developed in this paper.…”
Section: Discussionmentioning
confidence: 84%
“…One might hope that some extrapolation of our approach could shed further light on the discussion of [29]. in other recent studies of non-perturbative contributions to string scattering amplitudes [30][31][32][33] it was suggested that D-particle loops are related via T-duality to D-instanton contributions in IIB string theory. It clearly would be interesting to see if the suggestive formulas obtained in these works can possibly be reproduced via the Matrix string methods developed in this paper.…”
Section: Discussionmentioning
confidence: 84%
“…where P (2w) denotes an interaction between a set of fields with net U (1) charge 2w and Another interesting IIB amplitude which can be obtained in this way is the amplitude involving four self-dual five-form fieldsF 5 . The eleven dimensional vertex (5.34) gives the amplitude which involves (F 5 ) ilmn8 .…”
Section: Compactification On a Two Torus And Type Iib String Theorymentioning
confidence: 99%
“…The type IIB dilatino, λ, is identified with the gravitino of eleven-dimensional supergravity with its polarizations in appropriate directions. These calculations and generalizations were reviewed in [64] where some further details may be found, including a discussion of higher derivative contributions (which were also the subject of [22]).…”
Section: The Eleven-dimensional Perspectivementioning
confidence: 99%
“…After extracting the overall kinematic factor the remaining bosonic factor is simply the loop amplitude for the four-point amplitude in scalar φ 3 field theory. The full momentum dependence of this amplitude was discussed in [22,64]. Expanding in a power series in the momenta leads to higher derivatives acting on the fourth power of the curvature.…”
Section: The R 4 Term From One Loop In Eleven Dimensionsmentioning
confidence: 99%